Economic development in twentieth century East Asia : the international context - Ikeo, Aiko, 1956- (London ; New York : Routledge, 1997)
This collection supplies fascinating insights into aspects of East Asian economic development. It will interest scholars in a variety of related fields and provoke further research and debate.
Part iv: economic thought and reforms in developing china11. the concept of equal distribution of wealth in chinese social change since 1919; 12. does confucianism matter?; 13. the market economy and ethnic relations in china; index.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: East Asia -- Economic conditions -- Congresses; East Asia -- Foreign economic relations -- Congresses; Extrême-Orient -- Conditions économiques -- Congrès.; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; Economic history; International economic relations; East Asia; Electronic books; Conference papers and proceedings